Taguchi dynamic analysis application to computer tomography number-mass density linear dependence optimization. (31st October 2017) - Hsun-Nan, Kuo; Juei-En, Yi; Chia-Hui, Chen; Lung-Fa, Pan; Lung-Kwang, Pan
Abstract: The Taguchi dynamic analysis was applied to optimize the linear dependence between computer tomography (CT) number and mass density. The Taguchi unique L18 (2 1  × 3 5 ) orthogonal array was utilized in the dynamic analysis of a commercial Catphan 600 phantom with CTP 404 module, in order to optimize eighteen combinations of six factors controlling the CT simulator operation, i.e. scan time, kVp, mA, field of view (FOV), slice thickness, and imaging processing algorithm. Each factor being assigned two or three different levels made it possible to organize the required number of combinations (18). The seven materials involved in the phantom possessed different mass densities, which were incorporated into the dynamic analysis. The revised signal-to-noise ratio (S/N) was utilized to describe the integrated performance of various factors' combinations in pursuing the optimal ρm -CT number (HU) calibration curve. The optimal option was found to be: 1 s scan time, 130 kVp, 200 mA, 40 cm 2 FOV, 3 cm of slice thickness, and soft type of algorithm for maintaining the ρm -HU calibration. Factors kVp and FOV dominated the performance either by providing a significant change in S/N value or strongly improving the reproducibility in daily quality assurance. The ρm -HU calibration (HU = 1016.9 × density + 1029.5, r 2  = 0.9954) was further verified by the treatment planning systematic default (TPS) (HU= 1242.1 × density+ 1054.8, r 2  = 0.9755). The well-calibrated ρm -HU curve was successfully applied to clinical examination of the simulated oral cancer from CT scanned slice via a Rando phantom. A significant disagreement between optimal and default isodose curves was observed for doses exceeding 7000 cGy, while a good fit was exhibited by doses below 5000 cGy.